Effect of metadata on AI chatbot’s search results in enterprise search: An experimental study - Baburin, Mark (2025)
Artificial Intelligence has revolutionized enterprise search by enabling tasks beyond the capabilities of traditional information retrieval systems. However, enterprise search technology alone does not guarantee effective information retrieval. In this thesis, the effect of metadata on the search results of AI chatbot was investigated in the Microsoft Azure environment. The experimental study was conducted using 18 queries derived from the documents of the case company. The findings indicate that incorporating metadata in conjunction with an AI chatbot leads to a statistically significant enhancement in search performance.